Characterising the prognostic potential of HLA-DR during colorectal cancer development - Phelan, James; Dunne, Margaret (My University, 2020)
HLA-DR, an MHC class II molecule that mediates antigen presentation, is a favourable prognostic indicator in colorectal cancer (CRC). However, the dynamics and location of HLA-DR expression during CRC development are unclear. We aimed to define HLA-DR expression by immunohistochemistry in colorectal epithelium and stromal tissue at different stages of cancer development, assessing non-neoplastic colorectal adenocarcinoma–adjacent tissue, adenomas and carcinoma tissues, and to associate HLA-DR levels with clinical outcomes. Patients with higher than median HLA-DR expression survived at least twice as long as patients with lower expression. This association was significant for HLA-DR staining in the colorectal carcinoma epithelium (n = 152, p = 0.011, HR 1.9, 95% CI 1.15–3.15) and adjacent non-neoplastic epithelium (n = 152, p < 0.001, HR 2.7, 95% CI 1.59–4.66), but not stroma. In stage II cases, however, the prognostic value of HLA-DR expression was significant only in adjacent non-neoplastic tissues, for both epithelium (n = 63, p = 0.015, HR 3.6, 95% CI 1.279–10.25) and stroma (n = 63, p = 0.018, HR 5.07, 95% CI 1.32–19.49). HLA-DR was lower in carcinoma tissue compared to matched adenomas (n = 35), in epithelium (p < 0.01) and stroma (p < 0.001). HLA-DR was further reduced in late-stage carcinoma (n = 101) compared to early stage (n = 105), in epithelium (p < 0.001) and stroma (p < 0.01). HLA-DR expression was lower (p < 0.05) in the adjacent non-neoplastic epithelium of patients with cancer recurrence. We demonstrate a progressive loss of HLA-DR in epithelial and stromal tissue compartments during CRC development and show prognostic ability in carcinoma–adjacent non-neoplastic tissues, highlighting the importance of this molecule in the anti-cancer immune response. These findings may have wider implications for immunotherapeutic interventions.
PUBLISHED
Keywords: immunotherapeutic interventions.; HLA-DR, an MHC class II molecule; colorectal cancer (CRC); Adenoma; Cancer immunology; Cancer recurrence; Colorectal cancer; HLA-DR; Prognostic biomarkers; Cancer